Foraging ecology of the bird Eupsittula canicularis (Psittaciformes: Psittacidae) in a modified Mexican landscape - Flores-Yllescas, Itzel (2023)
Introduction: Seasonal phenological variations in tropical forests cause changes in food resource availability. Animals use foraging strategies to follow the food supply in these settings. The Orange-fronted Parakeet (Eupsittula canicularis) mainly inhabits the tropical dry forest of the Mexican Pacific to Northwest Costa Rica, although little is known about its diet and foraging strategies. Objective: To assess spatial variability in food resource abundance, diet, and foraging behavior of the Orange-fronted Parakeet in a modified landscape in Oaxaca Coast, Mexico. Methods: 30 phenology transects (200 × 6 m) were established during the dry season (February-June 2019) to measure food resource availability in primary deciduous, semi-deciduous, and secondary forests. The Orange-fronted Parakeets diet was determined by focal foraging observations, and dietary niche breadth and resource selection were considered to determine feeding strategies. Results: Orange-fronted Parakeets fed on fruits (42.3 %), seeds (29.3 %), and flowers (28.4 %) of 13 plant species and presented a broad dietary niche breadth with a higher frequency of foraging in primary forest. The Orange-fronted Parakeets select resources and adapt their foraging strategies based on food resource availability in each habitat. Conclusions: The study findings highlights the need to maintain the complete forest structure in a modified landscape to ensure food resources availability for Orange-fronted Parakeets during the breeding season.